PENGARUH FASILITAS DAN KOMPETENSI DOSEN TERHADAP MOTIVASI BELAJAR - Bahrudi Efendi Damanik (Jurnal Ekonomi dan Bisnis (EK&BI), 2019)
The purpose of this study was to determine the effect of facilities on learning motivation, the influence of lecturer competencies on learning motivation, the influence of facilities and lecturer competence on learning motivation. The population and sample in this study amounted to 81 people. The method used is a saturated sampling method, namely the technique of collecting data through interviews, surveys and questionnaires to respondents. The data analysis technique used in this study is multiple linear regression analysis, classic assumption test, t test, F test and determinant coefficient. The results of the analysis show that the facilities partially have a positive and significant effect on learning motivation, t count> t table (2,390> 1,664), lecturer competence partially has a positive and significant effect on learning motivation, t count> t table (4,229> 1,664), and facilities and Lecturer competencies together have a positive and significant influence on learning motivation, F count> Ftable (25,872> 2,720)